Octreotide: a new approach to the management of acute abdominal hypertension - ŞENER, GÖKSEL (ELSEVIER SCIENCE INC, 2003)
Acutely increased intra-abdominal pressure (IAP) may lead to abdominal compartment syndrome (ACS), which ischaemia/reperfusion (I/R) injury plays an important role. The main goal of the management of ACS is to lower the intra-abdominal pressure despite reperfusion injury. Octreotide (OCT), a synthetic somatostatin analogue, lowers the splanchnic perfusion. The aim of this study was to investigate whether OCT improves the reperfusion injury after decompression of acute abdominal hypertension. Under anesthesia, a catheter was inserted intraperitoneally and using an aneroid manometer connected to the catheter, IAP was kept at 20 mmHg (ischemia group; I) for 1 h. In the I/R group, pressure applied for an hour was decompressed and I h reperfusion period was allowed. In another group of I/R, OCT was administered (50 mug/kg i.p.) immediately before the decompression of IAP. The results demonstrate that kidney and lung tissues of malondialdehyde (MDA; an end product of lipid peroxidation) levels and myeloperoxidase (MPO; index of tissue neutrophil infiltration) activity were elevated, while glutathione (GSH; a key to antioxidant) levels were reduced in I/R group (P < 0.001). Moreover, OCT treatment applied in the I/R group reduced the elevations in blood urea nitrogen (BUN) and serum creatinine levels. Our results implicate that IAP causes oxidative organ damage and OCT, by reducing splanchnic perfusion and controlling the reperfusion of abdominal organs, could improve the reperfusion-induced oxidative damage. Therefore, its therapeutic role as a reperfusion injury-limiting agent must be further elucidated in IAP-induced abdominal organ injury. (C) 2003 Published by Elsevier Inc.
Keywords: abdominal hypertension; octreotide; myeloperoxidase; lipid peroxidation; glutathione; ISCHEMIA-REPERFUSION; COMPARTMENT SYNDROME; OXIDATIVE STRESS; MYELOPEROXIDASE ACTIVITY; BACTERIAL TRANSLOCATION; LIPID-PEROXIDATION; HEMORRHAGIC-SHOCK; TISSUE-INJURY; FREE-RADICALS; MELATONIN